Prime Symbols of the Transcendental Consiousness - Mickūnas, Algis (Sociologija. Mintis ir veiksmas, 1998)
The article analyzes the problem of defining the concept of consiousness in the modern sciences. The author notes that consiousness does exist in the form of reality, image, metaphycical pressuposition or human condition. Rather consiousness shows itseld as an expression of a specific phenomena beyond and before itself. The author develops a phenomenological analysis of the process of formation of consiousness in the context of symbolic formations, concepts and personal experiences. Change and steadiness, rules of interrelations as a phenomena can been seen as references and qualities through which a pre-symbolic consiousness of consciousness (or consiousness of prime symbols) appears.